2021
DOI: 10.3390/cancers13174383
|View full text |Cite
|
Sign up to set email alerts
|

How to Differentiate Benign from Malignant Adrenocortical Tumors?

Abstract: Adrenocortical carcinoma (ACC) is a rare cancer with a poor prognosis. Adrenal incidentalomas are, however, commonly identified in clinical practice. Discrimination between benign and malignant adrenal tumors is of great importance considering the large differences in clinical behavior requiring different strategies. Diagnosis of ACC starts with a thorough physical examination, biochemical evaluation, and imaging. Computed tomography is the first-level imaging modality in adrenal tumors, with tumor size and Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 162 publications
(264 reference statements)
0
19
0
1
Order By: Relevance
“…The presence of three or more of which was reported to be highly correlated with subsequent malignant behavior and is diagnostic of ACC [ 10 ]. The reported sensitivity and specificity were about 86–95% and 90%, respectively in expert hands [ 14 ]. However, borderline cases of adrenocortical neoplasm with uncertain malignant potential may challenge the reliability of the Weiss system, and these tumors often have a Weiss score of 1–3 [ 2 , 8 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of three or more of which was reported to be highly correlated with subsequent malignant behavior and is diagnostic of ACC [ 10 ]. The reported sensitivity and specificity were about 86–95% and 90%, respectively in expert hands [ 14 ]. However, borderline cases of adrenocortical neoplasm with uncertain malignant potential may challenge the reliability of the Weiss system, and these tumors often have a Weiss score of 1–3 [ 2 , 8 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being easier to use in clinical practice and more reproducible, the modified Weiss score has a reported specificity of 96.9% (vs. 90.2% in the original score) [ 7 ]. More recently, the reticulin algorithm and the Helsinki score ( Table 3 ) have been validated and are shown to be highly accurate in differentiating between benign and malignant adrenocortical tumors with 100% or nearly 100% sensitivity and specificity [ 3 , 4 , 14 ]. The rationale of the reticulin algorithm relies on the histochemical assessment of the reticulin network, which is commonly disrupted in ACC [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] A high expression of Nrf2 was reported to be associated with poor prognosis in ACC, 20 and an increased accumulation of 18 F-FDG was seen in the disease. 21 However, to date few studies have investigated the relationship of Weiss criteria and Helsinki score with Nrf2 from a metabolic perspective. In the present study, we found an association between a…”
Section: Discussionmentioning
confidence: 99%
“…The histological examination of adrenal tumors (including the Weiss-score and modified Weiss-score) is difficult and requires great expertise. Moreover, significant interobserver variability and a lack of accuracy in borderline cases are known limitations [ 8 ]. Mainly due to the difficulty of histological examinations, a biopsy of adrenal tumors is not recommended in routine practice and according to the current guidelines [ 3 , 5 ], as it would be difficult to determine malignancy from a small amount of tissue obtained, and there is a potential risk of complications (bleeding, pneumothorax) and maybe tumor dissemination as well [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%